PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS STEM TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Sihotang, Daniel; Ribka Kariani Sembiring; Imelda Sihombing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The aim of this study is to determine the effect of using the STEM-PJBL learning model on students’ creative thinking skills. This study is a quantitative quasi-experimental study. The population used in this study consists of all junior high school students at an A-accredited school in the Binjai Timur sub-district. The sample comprises two classes: Class VII A, which serves as the experimental class implementing STEM-based PJBL, and Class VII B, which serves as the control class receiving conventional instruction. The instruments used in this study are pre-test and post-test questions. The data analysis techniques in this study involved prerequisite tests (normality and homogeneity tests) and hypothesis testing using the t-test. The results of the independent samples t-test showed that the calculated t-value was greater than the critical t-value (2.390 > 1.675) and the significance level was 0.002, which is less than 0.05. Therefore, H₀ is rejected and H₁ is accepted. Consequently, it can be concluded that learning using the STEM-based PBL model has an effect on students’ creative thinking skills.